2021
DOI: 10.9734/ajfar/2021/v12i230228
|View full text |Cite
|
Sign up to set email alerts
|

A Mini-Review: Importance of Proper Nutrition for the Growth of Cultured African Catfish (Clarias gariepinus)

Abstract: Feeding is an important aspect of fish farming activities and could determine the quality of fish. African catfish (Clarias gariepinus) is an omnivorous freshwater fish that is high in protein and economical value. Catfish nursery generally uses natural feed and artificial feed to ensure the diet requirements fullfiled. Good feeding, in quality or quantity, is an important aspect to produce a high quality breed. A good feed is the basis of improving cultured catfish growth and survival performance. The purpose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…The average protein content in fish feed is 65% crude protein, but it may vary from 57-70% depending on the fish species. Another study found that the protein content in fish meals is 30% -38% [14]; 35%-45% [15]. The high protein content in catfish feed meal can be a substrate for hatching BSF larvae and affect the BSF larvae produced.…”
Section: Introductionmentioning
confidence: 99%
“…The average protein content in fish feed is 65% crude protein, but it may vary from 57-70% depending on the fish species. Another study found that the protein content in fish meals is 30% -38% [14]; 35%-45% [15]. The high protein content in catfish feed meal can be a substrate for hatching BSF larvae and affect the BSF larvae produced.…”
Section: Introductionmentioning
confidence: 99%